Abnormalities in P300 components in depression: an ERP-sLORETA study. (2nd January 2019) - Zhou, Lina; Wang, Gaohua; Nan, Cai; Wang, Huiling; Liu, Zhongchun; Bai, Hanping
Abstract: Background: Alterations in P300 components occur in depressed patients, but the brain regions contributing to these changes remain unclear. Aims: Thus, the aim of the present study was to examine the underlying neural activation of P300 components in patients with depression to explore brain regions related to depression. Methods: P300 components were evoked by an oddball auditory paradigm and recorded from 30 patients with current depression, as well as 30 age-, gender-, and education level-matched healthy controls. The standardized Low-Resolution Brain Electromagnetic Tomography (sLORETA) method was used to explore the source activation of P300 components. Results: Compared with healthy controls, depressed patients tended to exhibit lower P200 and P300 amplitudes and prolonged P300 latency. In depressed patients, P200 source activations were reduced in the right insula, right precentral gyrus, left anterior cingulate, medial frontal gyrus, superior frontal gyrus, and middle frontal gyrus. Decreased source activations of P300 were identified in the right insula, postcentral gyrus, superior temporal gyrus, inferior parietal lobule, transverse temporal gyrus, cingulate gyrus, precentral gyrus, middle frontal gyrus, superior frontal gyrus, medial frontal gyrus, and paracentral gyrus. Conclusions: Extensive dysfunction over the right hemisphere and bilateral prefrontal dysfunction may be involved in the pathophysiology of depression.